Rancang Bangun Sistem Detector Tiket Kereta Api Menggunakan RFID Berbasis Mikrokontroller - Roza Susanti; Albar albar; Ifni Joi; Agung Fitratana (Teknik Elektro Politeknik Negeri Padang, 2018)
The design of a prototype train ticket detector system using RFID-based microcontrollers has been made for replacing manual methods that still require officers to check tickets. This tool becomes a useful thing for a passenger to make easier going into the train departure room. The system made consists of 2 RFID units, 2 servo motors as an entrance and exit bar, an LCD circuit, and also facilitated with a buzzer circuit. This tool works when the RFID card is pasted to the RFID reader and the Arduino Uno Microcontroller will process the data whether the RFID card contains a balance and is sufficient to purchase train tickets. Then if the balance is sufficient, then the entrance gate bar is initially closed, it will open and the prospective passenger will enter the waiting room. However, If the balance is insufficient, the portal remains closed and the buzzer will be active and the balance will be displayed on the LCD. Furthermore, by pasting the RFID card on the exit portal crossbar to the RFID reader so the portal on the exit will open.